REFLECTION OF HADITH AND SUFISM IN MODERN LIFE: THE TRANSFORMATION OF ISLAMIC SPIRITUALITY IN THE DIGITAL ERA - Muiz, Abd.; Bukhori, Imam; Fidausi, Lailatul (Universitas Al-Amien Prenduan, 2025)
This study examines the reflection of hadith and Sufism in modern life, particularly in addressing the spiritual crisis faced by contemporary society in the digital era. Through qualitative analysis using a comprehensive literature review methodology, this research explores how classical Islamic spiritual teachings can be contextually adapted to meet contemporary challenges while maintaining their authentic essence. The study analyses various dimensions, including the relevance of prophetic traditions in solving modern problems, transforming Sufi practices in digital spaces, integrating spiritual values in professional life, and contributing Islamic mysticism to mental health. The findings indicate that hadith and Sufism remain highly relevant as spiritual foundations capable of addressing existential crises, meaning vacuum, and social alienation experienced by modern society. Digital technology, rather than eliminating spirituality, actually creates new spaces for spiritual practice and broader dissemination of Islamic teachings through applications, online communities, and digital platforms. However, digitalisation of spirituality requires careful attention to maintain authenticity and avoid reduction of spiritual experiences into mere digital content. The study concludes that successfully integrating hadith values and Sufi wisdom in modern life requires sophisticated hermeneutical approaches that enable contextual interpretation without compromising fundamental Islamic principles. This integration offers alternative solutions to materialism, individualism, and secularisation that characterise modern civilisation, while providing practical guidance for achieving spiritual balance in contemporary life.